Potential for transmission of naturally mutated H10N1 avian influenza virus to mammalian hosts and causing severe pulmonary disease - Zanin, Mark; Le, Tran Bac; Na, Woonsung; Kang, Jung-Ah; Kwon, Hyung-Jun; Hwang, Jaehyun; Ga, Eul Hae; Wong, Sook-San; Cho, Hae-Jin; Song, Daesub; Kim, Hye Kwon; Jeong, Dae Gwin; et al. (Frontiers in Microbiology, 2023)
Subtype H10 avian influenza viruses (AIV) are distributed worldwide in wild aquatic birds, and can infect humans and several other mammalian species. In the present study, we investigated the naturally mutated PB2 gene in A/aquatic bird/South Korea/SW1/2018 (A/SW1/18, H10N1), isolated from wild birds during the 2018–2019 winter season. This virus was originally found in South Korea, and is similar to isolates from mainland China and Mongolia. It had low pathogenicity, lacked a multi-basic cleavage site, and showed a binding preference for 2,3-linked sialic acids. However, it can infect mice, causing severe disease and lung pathology. SW1 was also transmitted by direct contact in ferrets, and replicated in the respiratory tract tissue, with no evidence of extrapulmonary spread. The pathogenicity and transmissibility of SW1 in mouse and ferret models were similar to those of the pandemic strain A/California/04/2009 (A/CA/04, H1N1). These factors suggest that subtype H10 AIVs have zoonotic potential and may transmit from human to human, thereby posing a potential threat to public health. Therefore, the study highlights the urgent need for closer monitoring of subtype H10 AIVs through continued surveillance of wild aquatic birds.